The Influence of Competence, Placement and Work Facilities on Lecturer Performance Through Motivation at Batang Hari Islamic University - Ayu Yuliani; Pantun Bukit; Ali Akbar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study was to determine the influence of competence, placement and work facilities directly and indirectly simultaneously and partially on the motivation and performance of lecturers; and to analyze the influence of motivation on the performance of UNISBA lecturers. The population and sample in this study were 65 Permanent Lecturers at Batanghari Islamic University. The researcher used a quantitative Descriptive approach, Path Analysis and Hypothesis Testing, namely the simultaneous F Test and partial t Test using the assistance of the IBN SPSS Version 25 program. This study concluded that competence, placement, and work facilities simultaneously and partially had a positive and significant effect on motivation with a total direct and indirect effect of 51.79%. However, the influence of competence, placement, and work facilities on lecturer performance had a significant effect simultaneously, but was not significant partially with a total direct and indirect effect of 46.76%. Meanwhile, motivation had a positive and significant effect on lecturer performance at Batang Hari Islamic University with a total direct and indirect effect of 44.62%.